Zona thinning with a noncontact diode laser in ICSI embryos from women of advanced age - Petersen, C. G.; Mauri, A. L.; Baruffi, RLR; Pontes, Anaglória [UNESP]; Franco, J. G. (Kluwer Academic/plenum Publ, 2002)
Purpose: the objective of this study was to determine if the zona thinning (ZT) technique improved the rates of implantation and clinical pregnancy for patients aged, greater than or equal to38 years submitted to an ICSI program.Methods: A total of 100 patients submitted to ICSI and aged, greater than or equal to38 years were divided in a prospective and randomized manner into two groups: Group I - patients submitted to ZT (n = 50); a laser diode with 1.48 mum wavelength (Fertilaser) was used for the ZT procedure with 1-2 irradiations of 10 ms applied to four different positions on the zona pellucida (ZP) of each embryo to thin 60-90% of the ZP (each point with a 15-20 mum length of ZT). Group II - patients with no ZT (n = 50). In both groups, embryo transfer was performed on the second or third day.Results: the age of Group I patients (39.8 +/- 1.3) did not differ (p = 0.67) from that of Group II patients (40 +/- 1.9). The number of oocytes retrieved at metaphase II from Group I (6.4 +/- 4.2) and Group II (6.8 +/- 5) was similar (p = 0.94). Normal fertilization rates and cleavage rates were similar (p = 0.78 and p = 0.63, respectively) for Group I (71.5 +/- 22% and 96.7 +/- 11%) and Group II (73.5 +/- 19.7% and 96 +/- 11%, respectively). The number of embryos transferred was similar (p = 0.53) for the two groups (Group I = 3.1 +/- 1.3; Group II = 2.9 +/- 1.1). The thickness of the ZP of Group I embryos (16.9 +/- 2.4 mum) did not differ (p = 0.97) from that of Group II embryos (16.9 +/- 2.3 mum). The rates of embryo implantation and clinical pregnancy per embryo transfer were similar (p = 0.67, p = 0.61) for Group I (7 and 16%, respectively) and for Group II (8.2 and 22%, respectively).Conclusions: These results suggest that ZT in the population aged, 38 years may have no impact on ICSI success rates. However, this conclusion is limited to a situation in which length of the laser ZT was less than or equal to 20 mum and the laser was applied to four different positions.
Keywords: advanced age; assisted hatching; implantation; intracytoplasmic sperm injection; laser; pregnancy; zona thinning